2018
DOI: 10.1126/scitranslmed.aar2718
|View full text |Cite
|
Sign up to set email alerts
|

KHS101 disrupts energy metabolism in human glioblastoma cells and reduces tumor growth in mice

Abstract: Pharmacological inhibition of uncontrolled cell growth with small-molecule inhibitors is a potential strategy for treating glioblastoma multiforme (GBM), the most malignant primary brain cancer. We showed that the synthetic small-molecule KHS101 promoted tumor cell death in diverse GBM cell models, independent of their tumor subtype, and without affecting the viability of noncancerous brain cell lines. KHS101 exerted cytotoxic effects by disrupting the mitochondrial chaperone heat shock protein family D member… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 61 publications
(96 reference statements)
0
57
0
Order By: Relevance
“…Consistent with the latter being an expected consequence of ionizing radiation (Azzam et al 2012), extracellular flux analysis 5 days after high-dose radiation (20 Gy) showed that basal oxygen consumption rate (OCR), and OCR following mitochondrial stress test, were significantly elevated in iNet, compared to Con and Rev conditions. This indicates an iNet phenotype-mediated ability of GBM cells to maintain their oxidative metabolism under radiation-induced stress, which has been shown to be required for GBM cellular fitness and viability (Polson et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with the latter being an expected consequence of ionizing radiation (Azzam et al 2012), extracellular flux analysis 5 days after high-dose radiation (20 Gy) showed that basal oxygen consumption rate (OCR), and OCR following mitochondrial stress test, were significantly elevated in iNet, compared to Con and Rev conditions. This indicates an iNet phenotype-mediated ability of GBM cells to maintain their oxidative metabolism under radiation-induced stress, which has been shown to be required for GBM cellular fitness and viability (Polson et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…We phenotypically characterized chemical ROCK inhibition in transcriptionally heterogeneous patient-derived GBM cell lines that represent different parental tumor origins and molecular GBM subtypes (Drubin et al 1985; Wurdak et al 2010; Wurdak 2012; King et al 2017; da Silva et al 2018; Polson et al 2018). We used adherent culture conditions, which conserved their stem cell-like characteristics (Wurdak et al 2010; Wurdak 2012; King et al 2017; da Silva et al 2018; Polson et al 2018). After treatment of five different cell lines with 20 μM ROCK inhibitor Y-27632, time lapse microscopy imaging revealed a pronounced elongation of cellular projections akin to cytokine-stimulated neurite outgrowth (Drubin et al 1985) ( Fig 1A, Videos S1-10 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we sought to confirm that this phenotype was also observed in patient-derived glioma stem-like cells (GSCs) as a more representative in vitro model. We used two previously characterized GSCs, GBM1 and GBM4 (23, 24) and performed new time courses for the flow cytometry assays at 72, 96 and 120 hours to reflect the slower division rate of the patient-derived cells, and we repeated the imaging experiments with binucleation scoring at 96 hours. Transfection of GBM1 with mimic miR-1300 caused a profound G2/M phase block with a 4-fold increase in the proportion of cells in G2/M phase at 72, 96 and 120 hours compared to cells transfected with the scrambled-mimic control (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…We used three patient derived GSC lines (described in Polson et al, 2018) shown to exhibit a stem celllike expression profile and recapitulate high-grade gliomas in orthopic xenograft mouse models (22,24), and performed cytotoxicity assays, using peripheral blood derived, IL-15 activated NK cells to confirm NK cell mediated killing. Tumour cells differentiated from GSCs are more sensitive to NK cell killing than the GSC themselves (26) but GSCs are killed by NK cells in the presence of activating cytokines ( Figure 1A) (25).…”
Section: Glioma Stem-like Cells Are Effective Targets Of Nk Cellsmentioning
confidence: 99%